.3x+8.6=.65x+10

Simple and best practice solution for .3x+8.6=.65x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .3x+8.6=.65x+10 equation:


Simplifying
0.3x + 8.6 = 0.65x + 10

Reorder the terms:
8.6 + 0.3x = 0.65x + 10

Reorder the terms:
8.6 + 0.3x = 10 + 0.65x

Solving
8.6 + 0.3x = 10 + 0.65x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.65x' to each side of the equation.
8.6 + 0.3x + -0.65x = 10 + 0.65x + -0.65x

Combine like terms: 0.3x + -0.65x = -0.35x
8.6 + -0.35x = 10 + 0.65x + -0.65x

Combine like terms: 0.65x + -0.65x = 0.00
8.6 + -0.35x = 10 + 0.00
8.6 + -0.35x = 10

Add '-8.6' to each side of the equation.
8.6 + -8.6 + -0.35x = 10 + -8.6

Combine like terms: 8.6 + -8.6 = 0.0
0.0 + -0.35x = 10 + -8.6
-0.35x = 10 + -8.6

Combine like terms: 10 + -8.6 = 1.4
-0.35x = 1.4

Divide each side by '-0.35'.
x = -4

Simplifying
x = -4

See similar equations:

| 13-20-(-2)= | | y=-4x^5+2x^4+6x+5 | | 25-2(7+5)= | | 36+35/5*4 | | 4(c-3)-6=6 | | -7(x+2)-18=25+6 | | 141/9-13/18 | | .4+.6x=.53+.5x+1.5 | | 3x^4-4x^3+x^2+6x-2= | | 2x+y=-400 | | -(1-2)-4= | | y=-3x^9+8x^6+7x^5+7 | | w=p(v-l) | | 8-(11-7)= | | 5/9+10 | | (4w-9)(5-w)=0 | | 9-3(-2-5)=30 | | 6m-8=2+9m-11 | | 2(z-1)=4(z+5)-10 | | 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 | | x^(2/3)-2x^(1/3)-8=0 | | 11-6y-19=7y+8-5y | | 6x+2+3x=9x+2 | | 64/5n-8/9=7/15n | | 11y-5y+6=-24-9y | | 6(7x-3)-4=42x-22 | | n^2-4n-35=0 | | 4y+9=-2y-9 | | 11=8x-8 |

Equations solver categories